let $f(0)=1$ and $f'(0)=1$.

and $f(x+y)=f(x)f(y)$ for $x,y\in R$.

How can I found $f(x)$ by using a definition of derivative?

  • $\begingroup$ What have you tried? And how could you use the definition of the derivative here to learn more about $f$? $\endgroup$ – TMM Sep 15 '11 at 13:34
  • $\begingroup$ $f(x+h)=f(x)f(h)$, $f(x+h)-f(h)=f(x)(f(h)-1)$, $\frac{f(x+h)-f(h)}{h}=f(x)\frac{f(h)-1}{h}$, $\lim_{h\to 0}$, then $f'(x)=f(x)$ $\endgroup$ – Xiang Sep 15 '11 at 13:39
  • $\begingroup$ If you get $f'(x) = f(x)$ you're done? $\endgroup$ – TMM Sep 15 '11 at 13:42
  • 3
    $\begingroup$ Well you can already show $f'=f$ and you know $f(0)=1 $so now can you prove that $ e^x $ is the unique solution to that Initial value problem? Hint: Assume $y=e^x g(x)$ solves the IVP and plug it in to see if you can say anything about what $g$ must be. $\endgroup$ – Ragib Zaman Sep 15 '11 at 13:46
  • 3
    $\begingroup$ If $f'(x) = f(x)$, then $f'(x) / f(x) = 1$. But $f'(x)/f(x) = \frac{d}{dx} \ln(f(x)) = 1$ implies $\ln(f(x)) = x + C$ and $f(x) = D e^x$. If of course you are allowed to use all that. $\endgroup$ – TMM Sep 15 '11 at 13:47

Let me just turn that last comment into an answer. As you already pointed out in the comments, by the definition of the derivative and using $f(x+y) = f(x)f(y)$, $f(0) = 1$ and $f'(0) = 1$ we have

$$f'(x) = \lim_{h\to 0} \frac{f(x+h)-f(x)}{h} = \lim_{h\to 0} \frac{f(x)f(h)-f(x)f(0)}{h} = f(x) \lim_{h\to 0} \frac{f(h)-f(0)}{h} = f(x) f'(0) = f(x)$$

Now you're almost done, as $f'(x) = f(x)$ is one of the essential properties of the exponential function. From $f'(x) = f(x)$ it follows that

$$\frac{f'(x)}{f(x)} = \frac{d}{dx}\left(\ln f(x)\right) = 1$$

Integrating both sides, we get $\ln f(x) = x + C$ for some constant $C$. This implies $f(x) = D e^x$ for some constant $D$ (i.e. $D = e^C$). We know that $f(0) = 1$, so it follows that $D = 1$ and $f(x) = e^x$.

Alternatively, as pointed out by Ragib, after noticing $f'(x) = f(x)$ you could write $f(x) = e^x g(x)$ for some function $g(x)$. Then $f'(x) = e^x g'(x) + f(x) = f(x)$, so $e^x g'(x) = 0$ for all $x$. Since $e^x \neq 0$, it follows that $g'(x) = 0$ and $g(x) = D$ is constant. Using $f(0) = 1$ it then follows that $D = 1$ and $f(x) = e^x$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.